Pengaruh etika kerja Islam dan penghayatan agama terhadap prestasi pekerja Bank Islam Malaysia Berhad di Negeri Kedah Darul Aman - Mohamed Idris, Mohamed Shahabudeen (2016)
Regardless of numerous studies on job performance, Islamic work ethics and religiosity in workplace, all of these topics continuously remain as the most popular topics discussed among researchers in the recent years. This is because of the continuance of unethical cases and lack of religious realization in the organizations which lead employees to disengage and not performing well. This is the reason why this study was conducted. This study put emphasizes on Islamic religiosity which encourage an individual to apply Islamic work ethics in daily live. Additionally, this study is intended to explore the view from an Islamic organization on the relationship between Islamic work ethics and religiosity on job performance. The findings of this study show a significant relationship on each variable and mediating effect of work engagement. The findings are supported by one main underpinning theory, namely Theory of Planned Behavior, which focuses on Perceived Behavioral Control. The article concludes with a discussion of the research findings, implications and limitations of the study, and recommendation for future research.